Information security of the region: Approaches to consideration and economic essence - Liubov Kovalska; Volodymyr Topalov; Roman Topalov (Економічний форум)
The article proves that the information space undergoes constant dynamism and transformation. It is noted that information resources need to be protected from threats and dangers of unauthorized access to them. The necessity of ensuring information security at various levels of management is proved. These levels are information security of the individual, information security of the enterprise, information security of the region, information security of the state. The literature review of the concept of “Information Security” is carried out. Approaches to the economic essence of information security are grouped according to three criteria: on the basis of “information protection from dangers and threats”; on the basis of “stable and stable state of the public administration system in the information space”; on the basis of “safe conditions for the existence of information technologies”. It is noted that state and regional government bodies should monitor possible information attacks, develop preventive actions to protect the information space of Ukraine. The necessity of developing preventive measures to localize and neutralize possible threats and dangers in the information space through the use of modern information technologies is proved. Modern information technologies can protect information, protect citizens from information attacks and preserve the integral information space of the country. The author's vision of information security of the region as a state of protection of information resources of regional business entities (information databases) from threats and environmental hazards for the implementation of national interests in the information sphere at the regional level and ensuring the information sovereignty of the country as a whole is presented